2021
DOI: 10.1007/s13555-021-00558-0
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab in Adults with Moderate-to-Severe Atopic Dermatitis and Prior Use of Systemic Non-Steroidal Immunosuppressants: Analysis of Four Phase 3 Trials

Abstract: Introduction: Dupilumab is approved as firstline systemic treatment for adults/adolescents with moderate-to-severe atopic dermatitis (AD) in Europe and elsewhere owing to its favourable benefit-risk profile. However, systemic nonsteroidal immunosuppressants (NSISS) are often used as first-line therapy in clinical practice. Impact of prior therapy with NSISS on dupilumab's treatment effect vs. control has not been described previously. This study assessed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
3
26
0
1
Order By: Relevance
“…A trend of high response to dupilumab at month 4 or month 12 was observed in patients with prior asthma, although the proportion of response to dupilumab at month 4 ( p = 0.074) was not significantly different from baseline in these patients. A previous study demonstrated that AD patients with prior systemic non-steroidal immunosuppressants (NSISS) (e.g., cyclosporine, methotrexate, azathioprine, or mycophenolate mofetil) use had a lower EASI reduction at week 16 than that in patients without prior NSISS use [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A trend of high response to dupilumab at month 4 or month 12 was observed in patients with prior asthma, although the proportion of response to dupilumab at month 4 ( p = 0.074) was not significantly different from baseline in these patients. A previous study demonstrated that AD patients with prior systemic non-steroidal immunosuppressants (NSISS) (e.g., cyclosporine, methotrexate, azathioprine, or mycophenolate mofetil) use had a lower EASI reduction at week 16 than that in patients without prior NSISS use [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matched healthy controls were recruited via advertisements. To reduce heterogeneity, the study inclusion criteria for subjects with AD were: 1) presence of atopy established by positive aeroallergen skin prick test and/or elevated serum total IgE levels; and 2) moderate-to-severe AD defined as an EASI score ≥ 17 and investigator global assessment score ≥ 3 [ 43 ]. These AD severity tools have previously been validated for AD severity scoring [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…To reduce heterogeneity, the study inclusion criteria for subjects with AD were: 1) presence of atopy established by positive aeroallergen skin prick test and/or elevated serum total IgE levels; and 2) moderate-to-severe AD defined as an EASI score ≥ 17 and investigator global assessment score ≥ 3 [ 43 ]. These AD severity tools have previously been validated for AD severity scoring [ 43 , 44 ]. Control subjects were included if they had no history of atopic disease and displayed negative results from aeroallergen skin prick testing performed at their enrollment visit.…”
Section: Methodsmentioning
confidence: 99%
“…AD affects the face, extensor surfaces of the body, fold of arms, legs, Sole, Palm and neck. The prevalence of AD is 20% (5%-30% in the paediatric and 1%-10% in the adult population) worldwide; 12%-14% in Africa; 6%-10% in Latin America; 3%-6% in Asian-Pacific countries, Eastern Mediterranean region, and India [5,6,7] . Over the last 40 years, the incidence of AD has risen, it appears to be commoner in urban & semi-urban areas than in rural areas and in the industrialised as opposed to less industrialised countries [6,7,8] .…”
Section: Introductionmentioning
confidence: 99%